SPHERE's 'Dress Sense' a Multi-disciplinary approach to designing wearable technology to improve health - Amelia Martin (Frontiers Media S.A., 2015)
Background Healthcare systems face financial challenges, with a greater number of the population living longer with long term conditions. In order to deliver safe, high quality care within these constraints, we must place more emphasis on preventing illness than treating illness. We can use the science of behaviour change, health, and technology to create solutions to these problems. An example of innovation in this field include SPHERE's multidisciplinary project entitled 'Dress Sense', with the aim to create a piece of wearable technology to improve health. Description This competition was run by SPHERE (Sensor Platform for HEalthcare in a Residential Environment) which focuses on developing sensor systems to monitor health and wellbeing in the home. The teams comprised of computer scientists, medical professionals, students and school children, engineers, fashion designers and textile artists. They were provided with a kit including Arduino software, sensors and other items to make wearable computers. There were no constraints on what they could produce, except for a deadline of 3 weeks. The end project was judged according to the innovation and usefulness of the overall concept; the functionality, usability and desirability (aesthetics) of the constructed device and the multi-displinary component. The idea was to foster open innovation in order to share ideas between specialities. Conclusions Ideas included tackling diabetic medical adherence through a wearable band to sensors woven into socks to prevent deep vein thrombosis. The winning concept was, 'Yo' a support system to aid cognitive behaviour therapy, through wearable products and accessories, to help those who begin CBT, stay motivated to engage effectively with therapy. This project highlighs how through multi-disciplinary collaboration and including the younger generation, innovative effective ideas can be found to harness digital technology to improve health.